Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China - Deng, Wei-An; Zheng, Zhe-Min; Wei, Shi-Zhen (Zootaxa, 2016)
Taxonomy of a tetrigid genus Gibbotettix Zheng is reviewed. Two new species, Gibbotettix serrifemurus sp. nov. and Gibbotettix parvipulvillus sp. nov. are described from China.The distribution and an updated identification key to all known species of the genus are given.